2023
DOI: 10.3390/su151411253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Enablers of Green Entrepreneurship in Circular Economy: Organizational Enablers in Focus

Maryam Soleimani,
Elahe Mollaei,
Mojgan Hamidi Beinabaj
et al.

Abstract: In recent decades, green entrepreneurship has been at the center of attention as an effective strategy to maintain sustainability and create a competitive advantage for organizations in a circular economy. However, the successful implementation of this strategy requires organizations to have internal enablers. This study endeavored to identify and evaluate organizational enablers for green entrepreneurship in manufacturing Small and Medium Enterprises (SMEs) in Iran. Identifying organizational enablers can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…It validates evidence from overseas where one study discovered public subsidies positively and significantly promoted innovation input and output of 2600 Chinese SMEs [46], and another study indicated research and innovation funding benefitted 1860 European Union SMEs [47]. Recent research from a study in Iran underscores that green entrepreneurship can be a strategically effective way to foster circularity, but organizational enablers are required to adopt such entrepreneurship in manufacturing SMEs [48].…”
Section: Discussionsupporting
confidence: 70%
“…It validates evidence from overseas where one study discovered public subsidies positively and significantly promoted innovation input and output of 2600 Chinese SMEs [46], and another study indicated research and innovation funding benefitted 1860 European Union SMEs [47]. Recent research from a study in Iran underscores that green entrepreneurship can be a strategically effective way to foster circularity, but organizational enablers are required to adopt such entrepreneurship in manufacturing SMEs [48].…”
Section: Discussionsupporting
confidence: 70%
“…This supply chain refers to supply chain management for food waste that can be carried out systematically and relevant to the existing industrial supply chain. A recent study in circular supply chain management (CSCM) explained that supply chain management and natural and industrial ecosystems around it should count the circular thinking (Soleimani et al, 2023). In CSCM, technical materials are recovered automatically, and biological materials are regenerated through extensive innovation in business models and supply chain operations (Rai et al, 2019).…”
Section: Sustainable Food Waste Management In Green Startupmentioning
confidence: 99%
“…Suriyankietkaew et al [3], through a bibliometric review, illustrated how strategic management can be used to achieve all three dimensions of sustainability. Entrepreneurship has, as its primary objectives, the expansion of an enterprise and the generation of wealth [4,5]. This is true for all economic types, whether developed or developing [6].…”
Section: Introductionmentioning
confidence: 99%